OHP-026 Economic Evaluation of Antifungal Drugs in an Intensive Care Unit. (12th March 2013) - Cattel, F; Chiumente, M; Ancona, F; Miliacca, A; De Rosa, FG; Scaldaferri, M; Sciorsci, E; Re, F; Stecca, S
Abstract : Background: Anidulafungin is a semisynthetic echinocandin, mainly used in invasive Candida infections in non-neutropenic patients, with a daily dose cost lower than other antifungal drugs used in candidiasis treatment. Purpose: To prepare a mathematical model, able to produce an estimate of the savings that could be realised using anidulafungin instead of the other antifungals. Materials and Methods: A pilot study was carried out at Turin hospital 'Città della Salute e della Scienza', involving two Intensive Care Units (ICUs), which are the major consumers of echinocandins. In these two ICUs: Data concerning consumption, prices and 2010 rebates for various antimycotics were collected; The medical records of 174 patients, admitted in 2010, were examined to identify all those instances where anidulafungin could have been appropriately used, instead of other antifungals. Based on the analysis of medical records, the substitution index of the other antimycotics with anidulafungin has enabled us to calculate its potential use and the saving that the hospital might be able to achieve. Results: The analysis revealed a frequently inappropriate use of various antifungal drugs. The review of medical reports confirmed a 70% substitution index of liposomal amphotericin B with anidulafungin. In 2010, the hospital used 9, 237 vials of caspofungin, anidulafungin and liposomal amphotericin B. If we assume 100% use of anidulafungin in instances where it would be appropriate in the two ICUs, the hospital could make savings exceeding Euro 100, 000 per year. Results: The ICUs in question account for 18% of the total vials. The possible savings that could be made by extending the analysis and application of the mathematical model to the entire hospital have not yet been investigated, but the model has confirmed the initial assumption of possibly saving money by using anidulafungin, according to approved indications, in substitution for other antimycotic drugs. No conflict of interest.